Thai Children’s Games Suite for Wind Symphony: A Creative Research in Music Composition - Tagosa, Woraket (Rangsit Music Journal, 2024)
A Creative Research in Music Composition: Thai Children’s Games Suite for Wind Symphony (Grant No. RGNS 63-244) was supported by Office of the Permanent Secretary, Ministry of Higher Education, Science, Research and Innovation (OPS MHESI), Thailand Science Research and Innovation (TSRI) and Assumption University. This research aims to create contemporary music compositions for small and large ensembles of wind instruments in the form of program music which reflect stories of Thai children’s games. The results of the research found that there are four new compositions with a total length of approximately 35 minutes, consisting of (1) Thai Children’s Games Suite for Woodwind Quartet, (2) Mon Son Pha for Wind Symphony, (3) Ree Ree Khao San for Wind Symphony, and (4) Ngoo Kin Hang for Wind Symphony. The researcher integrates compositional concepts and techniques such as converting poems from the games into melodies, melodic quotations, Idée fixe, swing jazz, ramwong, march, ostinatos, chromatic scale, octatonic scale, and pentatonic scale. The research perfectly and successfully achieved all its objectives, resulted in academic works that blend the aesthetics of classical music, jazz, and Thai folk music which can be applied or developed further both academically and commercially, as well as enhancing pride in the folk cultures.